2008
DOI: 10.2478/v10026-008-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of phenol from aqueous solution by burned water hyacinth

Abstract: The potential of burned water hyacinth (BWH) for phenol adsorption from aqueous solution was studied. Batch kinetic and isotherm studies were carried out under varying experimental conditions of contact time, phenol concentration, adsorbent dosage and pH. The pH at the point of zero charge (pH PZC ) of the adsorbent was determined by the titration method and the value of 8.8 ± 0.2 was obtained. The FTIR of the adsorbent was carried out in order to find the potential adsorption sites for the interaction with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 34 publications
8
69
0
1
Order By: Relevance
“…Thus, with an increase in adsorbent dosage, the amount of dye adsorbed onto unit weight of adsorbent gets reduced causing a decrease in q value. Similar behavior has been reported in case of adsorption of Congo Red (Rajamohan 2009) and phenol (Uddin et al 2008) onto water hyacinth root.…”
Section: Resultssupporting
confidence: 84%
“…Thus, with an increase in adsorbent dosage, the amount of dye adsorbed onto unit weight of adsorbent gets reduced causing a decrease in q value. Similar behavior has been reported in case of adsorption of Congo Red (Rajamohan 2009) and phenol (Uddin et al 2008) onto water hyacinth root.…”
Section: Resultssupporting
confidence: 84%
“…This result indicates that up to 90-95 % of the total phenol uptake occurs in the first rapid phase (60 min) and thereafter the adsorption rate is decreased. The higher adsorption rate at the initial period (first 40 min) may be due to large number of vacant sites on the adsorbent and as a result there exist increased concentration gradients between adsorbate in solution and adsorbate on adsorbent surface (Uddin et al 2007). ANN model prediction in accordance with the experimental data (Fig.…”
Section: Effect Of Contact Timesupporting
confidence: 63%
“…The percentage removal of phenol increased with the increasing absorbent dosage (0.5-4.0 g). It is attributed due to increase in adsorbent surface area and availability of more adsorption sites (Mehrizad et al 2009;Uddin et al 2007). The results also revealed that the adsorption efficiency increases with the increasing dose (Rengaraj et al 2002).…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 99%
See 2 more Smart Citations